1985
DOI: 10.1111/j.1440-1827.1985.tb00587.x
|View full text |Cite
|
Sign up to set email alerts
|

Familial Occurrence of Oligomeganephronia

Abstract: Oligomeganephronia (OMN) is a rare, renal hypoplasia, consisting of reduced number of hypertrophied nephrons. This disorder has been considered to be a congenital but not a genetic disease. We describe the first report, to the best of our knowledge, of familial cases of OMN; two male siblings ran rapidly downhill courses and died 11 and 8 days after births, respectively. In addition, the two patients had similar multiple anomalies; microcephaly, prominent glabella, hypertelorism, antimongoloid slant, epicantha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Pathogenesis of oligomeganephronia is not fully understood but is believed to reflect premature interruption of nephrogenesis. 2,10 Most cases are sporadic, but familial occurrence has been described. 2,4 Although oligomeganephronia may be an isolated anomaly, it also occurs in genetic syndromes such as renal-coloboma syndrome (renal hypoplasia and optic nerve coloboma associated with PAX2 gene mutations on chromosome 10) and branchio-oto-renal syndrome [branchial cysts or fistulae, hearing impairment, and ear and renal anomalies associated with EYA1 (chromosome 8) and other gene mutations].…”
Section: Discussionmentioning
confidence: 99%
“…Pathogenesis of oligomeganephronia is not fully understood but is believed to reflect premature interruption of nephrogenesis. 2,10 Most cases are sporadic, but familial occurrence has been described. 2,4 Although oligomeganephronia may be an isolated anomaly, it also occurs in genetic syndromes such as renal-coloboma syndrome (renal hypoplasia and optic nerve coloboma associated with PAX2 gene mutations on chromosome 10) and branchio-oto-renal syndrome [branchial cysts or fistulae, hearing impairment, and ear and renal anomalies associated with EYA1 (chromosome 8) and other gene mutations].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a great majority of patients with oligomeganephronia are sporadic cases with no associated anomalies. However, if they are associated with multiple anomalies they usually belong to one of following categories; 1) combination of hearing loss, ocular abnormalities, mental retardation, convulsions, and abnormal EEG (10) ; 2) association with congenital eye and skeletal abnormalities (1 1 ) ; 3) association with acral anomalies (8); 4) association with tapetoretinal degeneration (12); 5) association with branchio-oto-renal syndrome (13) ; or 6) associations with 4p monosomy-type multiple anomalies (14). Our cases certainly belong to category 5 of this classification.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the first five settings are seen in 4p deletion-type chromosomal anomaly ( 15). Although the cases of Kusuyama et al ( 14) actually had normal Gband karyotypes, they suggested 4p monosomy syndrome phenotypically. When we saw cases with similar multiple anomalies associated with oligomeganephronia, we were interested in knowing its relationship to certain chromosomal aberrations.…”
Section: Introductionmentioning
confidence: 96%
“…Congenital oligomeganephronia, in which glomeruli are few, very large, and prone to sclerosis (38,39), is one blatant model of nephron underendowment. Although most cases are sporadic, it sometimes occurs in family clusters, suggesting a genetic background (40), and an association with PAX2 gene mutations has been described (41). More modest deficiencies of nephron endowment might be part of the same spectrum (31).…”
Section: Geneticsmentioning
confidence: 99%
“…Proliferation of nephrons is particularly rapid in the last trimester, continuing up through the 36th week, then it ceases (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The final complement of nephrons, which is reflected in kidney volume estimates by ultrasound, as well as in kidney mass and nephron number, is critically dependent on two factors: gestational age and a favorable intrauterine environment.…”
Section: Early Life Influencesmentioning
confidence: 99%